International variation in survival after out-of-hospital cardiac arrest: A validation study of the Utstein template - Dyson, K.; Brown, S.P.; May, S.; Smith, K.; Koster, R.W.; Beesems, S.G.; Kuisma, M.; Salo, A.; Finn, Judith; Sterz, F.; Nürnberger, A.; Morrison, L.J.; et al. (ELSEVIER IRELAND LTD, 2019)
Introduction: Out-of-hospital cardiac arrest (OHCA) survival varies greatly between communities. The Utstein template was developed and promulgated to improve the comparability of OHCA outcome reports, but it has undergone limited empiric validation. We sought to assess how much of the variation in OHCA survival between emergency medical services (EMS) across the globe is explained by differences in the Utstein factors. We also assessed how accurately the Utstein factors predict OHCA survival. Methods: We performed a retrospective analysis of patient-level prospectively collected data from 12 OHCA registries from 12 countries for the period 1 Jan 2006 through 31 Dec 2011. We used generalized linear mixed models to examine the variation in survival between EMS agencies (n = 232). Results: Twelve registries contributed 86,759 cases. Patient arrest characteristics, EMS treatment and patient outcomes varied across registries. Overall survival to hospital discharge was 10% (range, 6% to 22%). Overall survival with Cerebral Performance Category of 1 or 2 (available for 8/12 registries) was 8% (range, 2% to 20%). The area-under-the-curve for the Utstein model was 0.85 (Wald CI: 0.85–0.85). The Utstein factors explained 51% of the EMS agency variation in OHCA survival. Conclusions: The Utstein factors explained 51% of the variation in survival to hospital discharge among multiple large geographically separate EMS agencies. This suggests that quality improvement and public health efforts should continue to target modifiable Utstein factors to improve OHCA survival. Further study is required to identify the reasons for the variation that is incompletely understood.